The thin blue line - Glass, Philip 1937- (<<The>> Criterion Collection, 2015)
"Among the most important documentaries ever made, "The Thin Blue Line", by Errol Morris, erases the border between art and activism. A work of meticulous journalism and gripping drama, it recounts the disturbing tale of Randall Dale Adams, a drifter who was charged with the murder of a Dallas police officer and sent to death row, despite evidence that he did not commit the crime. Incorporating stylized reenactments, penetrating interviews, and haunting original music by Philip Glass, Morris uses cinema to build a case forensically while effortlessly entertaining his viewers. "The Thin Blue Line" effected real-world change, proving film's power beyond the shadow of a doubt." [criterion.com]
Aspect ratio 1.78:1. - New high-definition digital restoration
Orig.: USA 1988
Enth. new interview with Morris ; new interview with Joshua Oppenheimer, director of "The act of killing" ; NBC report from 1989 covering Randall Adams's release from prison" ; an essay by film scholar Charles Musser
Keywords: Adams, Randall Dale -- 1948-2010; Todesstrafe; Mord; Dokumentarfilm; Justizirrtum; Aufklärung; Texas; Film; DVD-Video